MHC-independent αβT cells: Lessons learned about thymic selection and MHC-restriction - Van Laethem, François; Bhattacharya, Abhisek; Craveiro, Marco; Lu, Jinghua; Sun, Peter D.; Singer, Alfred (Frontiers in Immunology, 2022)
Understanding the generation of an MHC-restricted T cell repertoire is the cornerstone of modern T cell immunology. The unique ability of abT cells to only recognize peptide antigens presented by MHC molecules but not conformational antigens is referred to as MHC restriction. How MHC restriction is imposed on a very large T cell receptor (TCR) repertoire is still heavily debated. We recently proposed the selection model, which posits that newly re-arranged TCRs can structurally recognize a wide variety of antigens, ranging from peptides presented by MHC molecules to native proteins like cell surface markers. However, on a molecular level, the sequestration of the essential tyrosine kinase Lck by the coreceptors CD4 and CD8 allows only MHC-restricted TCRs to signal. In the absence of Lck sequestration, MHC-independent TCRs can signal and instruct the generation of mature abT cells that can recognize native protein ligands. The selection model thus explains how only MHC-restricted TCRs can signal and survive thymic selection. In this review, we will discuss the genetic evidence that led to our selection model. We will summarize the selection mechanism and structural properties of MHC-independent TCRs and further discuss the various non-MHC ligands we have identified.